2018
DOI: 10.1007/s11657-018-0435-7
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D levels and bone mineral density evaluation in patients with cholecystectomy: a case-control study

Abstract: In the light of our results, cholecystectomy patients seem to have lower level of 25(OH) D levels in comparison with healthy subjects, but both groups have similar BMD values. Further studies in cohort designs taking into account the bone formation and resorption markers are awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…In several previous studies, lower vitamin D level and lower BMD was noted in patients with previous cholecystectomy ( 20 , 21 ). On the other hand, other studies showed a lower vitamin D level but similar BMD following cholecystectomy ( 22 , 23 ). The discrepancy may be due to the small sample size of these studies.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In several previous studies, lower vitamin D level and lower BMD was noted in patients with previous cholecystectomy ( 20 , 21 ). On the other hand, other studies showed a lower vitamin D level but similar BMD following cholecystectomy ( 22 , 23 ). The discrepancy may be due to the small sample size of these studies.…”
Section: Introductionmentioning
confidence: 80%
“…To the best of our knowledge, this is the first study to investigate the incidence of fracture in participants who underwent cholecystectomy. To date, only a few published papers have evaluated the possible relationship between osteoporosis and cholecystectomy (20)(21)(22)(23)30). Osteoporosis is a common health problem with an increased financial burden; osteoporotic fracture is the most worrying complication of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that individuals undergoing cholecystectomy were at a higher risk of vertebral fractures at a younger age (<50yrs). Literature supports the harmful effect of cholecystectomy on VD status; however, the mechanistic relationship of VD absorption with cholecystectomy and lower serum 25(OH)D levels needs further elaboration (8)(9)(10).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…In postmenopausal osteoporotic females, serum VD levels were lower in comparison to serum resistin levels, and VD was declared to be a negative predictor of increased serum resistin concentration. The research proposes that hypovitaminosis D is a risk factor for IR independent of adiposity ( 10 ).…”
mentioning
confidence: 99%